(untitled) (International journal of artificial intelligence, 2026)
The article reveals the socio-philosophical essence of cultural and moral principles and criteria of ecological relations to nature. The interrelation of national and universal ecological and moral values in the context of global environmental problems is analyzed. The study substantiates the role of spiritual and moral norms in regulating relations in the "nature-society-human" system. The significance of the value system in the formation of ecological culture is shown. Mechanisms for the practical implementation of ecological and moral norms in the context of Uzbek society are proposed. The issues of strengthening the role of the mahalla institute, mass media and civil society actors in environmental education are studied. The author has developed institutional foundations for the development of ecological culture.